Effect of Dietary Supplementation with Different Levels of Palm Pollen on the Physiological Performance of the Broiler - Ezzat , Hasanain N. (International Journal of Poultry Science, 2018)
Objective: This experiment was conducted to study the effects of Palm pollen on the levels of lipids, proteins, enzymes, glucose, phosphorus, calcium and uric acid concentrations in the blood of broilers. Materials and Methods: Ninety-six chicks of the Ross 308 breed of both sexes, with an initial weight of 38 g/chick, were used. Chicks were distributed randomly into 4 treatment groups with 3 replicates (8 birds/replicate). Experimental treatments were divided as follows: T1-Control, T2-diet supplemented with palm pollen 200 g/100 kg, T3-diet supplemented with palm pollen 400 g/100 kgt and T4-diet supplemented with palm pollen 600 g/100 kg. A completely randomized design (CRD) was used to investigate the effects of the studied treatments on different traits. Results: The plasma lipid panel indicated that there were no significant differences among treatments for all characteristics in the 3rd and 5th weeks of the experiment, except for cholesterol and low-density lipoprotein (LDL) in the 3rd week, where the supplemented treatment resulted in a significant decrease for these characteristics. The results of the blood enzyme test indicated that T1 resulted in significantly increased (p